PENGARUH PROFITABILITAS, CAPITAL ADEQUACY RATIO DAN DIVERSIFIKASI PENDAPATAN TERHADAP RISIKO BANK (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Ulan Lestiana Putri; Risal Rinofah; Mujino Mujino (Jurnal Fokus Manajemen Bisnis, 2020)
The research aims to determine the influence of profitability, Capital Adequacy Ratio and revenue diversification against the risk of Bank. This study used case study on the banking companies and used the banks listed on the Indonesia Stock Exchange (IDX) in period 2014-2018 as the population. The research used purposive sampling technique.The data analysis techniques used statistical descriptive test, classical assumption testing (normality test, autocorrelation test, multicolinearity test, and heteroskedasticity test). Hypothesis testing used multiple linear regression analysis. The data quality testing used T test, F test and determination test. The results showed that profitability, Capital Adequacy Ratio partially had a negative and significant influence on the bank risk, while the revenue diversification had a positive influence on the bank risk. Simultaneously, the profitability, CAR and diversification of revenues had a significant influence on the bank risk.